The journey - Chiu; Heng, Yee Jia; Pfeiffer, Ben Andrew; Lee, Sai Peng; Joanne, Yew Hong Im (Kuala Lumpur : Astro Shaw Sdn. Bhd., 2013)
Uncle Chuan is an old-fashioned and conservative man staying alone in Cameron Highlands leading a lonely retired life. His hope is to reunite with his only daughter Ah Bee who will be returning from overseas after graduation and stay together as a traditional family. Finally Ah Bee came back after graduation but she brought back her foreign boyfriend Benji with her and they planned to get married. Uncle Chuan vigorously opposed to the marriage due to Ben's frivolous behavior but he failed to change his daughter's mind. At the end, Uncle Chuan agreed to their marriage reluctantly, with a condition to be fulfilled- their wedding ceremony must be a Chinese ceremony.
Special features: OST ; testimonial ; interview ; trailer.
Executive producer, Choo Chi Han, KC Cheong, KC Chuan, Kabir Ariff Sultan ; music director, Alex San ; editor, Gywneth Lee.
Ben Andrew Pfeiffer, Lee Sai Peng, Joanne Yew Hong Im.
LPF: U
DVD format, Widescreen (16:9).
In Mandarin, Cantonese, Hokkien with optional Chinese, English and Malay subtitles.
Keywords: Families in motion pictures; Love in motion pictures